2011
DOI: 10.1258/td.2010.100310
|View full text |Cite
|
Sign up to set email alerts
|

A survey of neonatal tetanus at a district general hospital in north-east Nigeria

Abstract: Neonatal tetanus (NNT) remains among the leading causes of morbidity and mortality in Nigeria and a huge challenge in achieving the fourth goal of the Millennium Development Goals. We reviewed the morbidity and mortality pattern among neonates with NNT admitted to the District General Hospital in north-east Nigeria from 2006 to 2009. Half of the patients were from rural areas and were delivered at home by untrained traditional birth attendants with no prior antenatal health care. Razor blades and scissors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This finding is similar to previous findings7892023 There were no cases of circumcision or ear piercing recorded as probable portal of entry.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar to previous findings7892023 There were no cases of circumcision or ear piercing recorded as probable portal of entry.…”
Section: Discussionsupporting
confidence: 92%
“…Available data indicates that 18 states (out of 37) are at risk for maternal and neonatal tetanus 4. Many hospital based studies have identified neonatal tetanus as a problem of high magnitude in Nigeria 5678. Maternal immunization and improved obstetric and neonatal care are the main strategies in Nigeria for improving protection against neonatal tetanus 4.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no further sterilization of the tools due to a belief that “new is clean.” Razor blades are readily available from most shops and chemists; typically these razor blades are wrapped in wax paper and exposed to open air and dust, which raises concern for tetanus or other forms of bacteria. Although a study from Sudan found the type of tool used to cut the cord not significantly associated with neonatal tetanus [39], there is ample evidence to support that unsterilized tools may increase the risk of neonatal tetanus or omphalitis [13,37,40,41]. …”
Section: Discussionmentioning
confidence: 99%
“…(1) vaccination of potential childbearing women and pregnant women; the vaccination schedule should be updated or initiated during prenatal care using tetanus toxoid, a lowcost and effective measure. (1,8,36) Table 3 shows the basic immunization schedule that was proposed by the Brazilian Ministry of Health and the Brazilian Pediatrics Society.…”
Section: Prophylaxis and Controlmentioning
confidence: 99%